A cervical sympathetic chain schwannoma of the left parapharyngeal space, presenting in the prestyloid region - Gupta, Manish; Singh, Sunder; Gupta, Monica; Kaur, Rupinder (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Extracranial schwannomas in the head and neck region are rare neoplasms. The tumours often present as asymptomatic, slowly enlarging lateral neck masses. Though the computed tomogram criteria for differentiating vagal and sympathetic chain schwannoma is acceptable in most cases, but rarely the clinician may be misled in very large schwannoma of sympathetic chain where determination of the nerve of origin may be impossible until surgical exploration.